Imaging in tuberculosis - Skoura, Evangelia; Zumla, Alimuddin; Bomanji, Jamshed (International journal of infectious diseases, 2015)
•The early diagnosis of tuberculosis (TB) is mandatory for effective treatment and control.•Chest radiography is essential in the diagnosis of primary pulmonary TB.•Computed tomography (CT) is the preferred imaging modality for lymphadenopathy, bronchogenic spread, and abdominal TB.•Magnetic resonance imaging is the preferred modality in tuberculous spondylitis and central nervous system TB.•Positron emission tomography (PET)/CT is the preferred modality in the assessment of anti-TB treatment response. Early diagnosis of tuberculosis (TB) is necessary for effective treatment. In primary pulmonary TB, chest radiography remains the mainstay for the diagnosis of parenchymal disease, while computed tomography (CT) is more sensitive in detecting lymphadenopathy. In post-primary pulmonary TB, CT is the method of choice to reveal early bronchogenic spread. Concerning characterization of the infection as active or not, CT is more sensitive than radiography, and 18F-fluorodeoxyglucose positron emission tomography/CT (18F-FDG PET/CT) has yielded promising results that need further confirmation. The diagnosis of extrapulmonary TB sometimes remains difficult. Magnetic resonance imaging (MRI) is the preferred modality in the diagnosis and assessment of tuberculous spondylitis, while 18F-FDG PET shows superior image resolution compared with single-photon-emitting tracers. MRI is considered superior to CT for the detection and assessment of central nervous system TB. Concerning abdominal TB, lymph nodes are best evaluated on CT, and there is no evidence that MRI offers added advantages in diagnosing hepatobiliary disease. As metabolic changes precede morphological ones, the application of 18F-FDG PET/CT will likely play a major role in the assessment of the response to anti-TB treatment.